Targeting LHPP in neoadjuvant chemotherapy resistance of gastric cancer: insights from single-cell and multi-omics data on tumor immune microenvironment and stemness characteristics - You-Xin Gao; Xiao-Jing Guo; Bin Lin; Xiao-Bo Huang; Ru-Hong Tu; Mi Lin; Long-Long Cao; Qi-Yue Chen; Jia-Bin Wang; Jian-Wei Xie; Ping Li; Chao-Hui Zheng; et al. (Cell Death and Disease)
Abstract Gastric cancer (GC) is a highly heterogeneous and complex malignancy, often characterized by tumor stemness and immune evasion mechanisms, which contribute to a poor response to neoadjuvant chemotherapy (NAC) and treatment resistance. In this study, we performed a comprehensive analysis using single-cell and multi-omics approaches on 375 GC samples from The Cancer Genome Atlas database, along with 141 clinical samples from patients who underwent NAC. We identified key gene modules associated with stemness and immune traits, and developed a novel stem cell-immune risk score. This score effectively distinguished responders from non-responders to chemotherapy, and was significantly associated with overall survival. Through multi-omics analysis, we further elucidated the role of phospholysine phosphohistidine inorganic pyrophosphatase (LHPP) in the tumor immune microenvironment. Our findings showed that high LHPP expression was closely linked to the increased infiltration of antitumor immune cells, such as CD8+ T cells, and significantly suppressed the development of stemness characteristics in GC. Additionally, single-cell sequencing data revealed that tumor epithelial cells with low LHPP expression exhibited heightened stemness and demonstrated the strongest communication with CD8+-exhausted T cells. We also observed that LHPP inhibited stemness and chemotherapy resistance in GC cells by regulating the phosphorylation of GSK-3β. In conclusion, LHPP plays a critical regulatory role in the stemness features and tumor immune microenvironment of GC, presenting a promising biomarker and potential therapeutic target for personalized treatment of GC.